EFEKTIVITAS PENYELENGGARAAN PROGRAM BEASISWA PEMERINTAH PROVINSI SUMATERA UTARA - Fina Mulyana (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
This research aims to determine the effectiveness of the implementation o f the North Sumatra Provincial Government (Pemprov) scholarship program, find out what obstacles are encountered in implementing the scholarship program and how the people of North Sumatra respond to the scholarship program. This research is qualitative research with a case study approach and data collection techniques through direct observation and interviews. This research was located at the North Sumatra governor's office, people's welfare bureau. The results found were that the implementation of the North Sumatra Provincial Government (Pemprov) scholarship program was not fully effective. During the implementation of the program, several obstacles were encountered: 1) Lack of information circulated by the organizers, 2) inappropriate governance of the scholarship program mechanism, 3) many requirements given in submitting scholarship proposals.